MENINGKATKAN NILAI PRODUK KULINER MELALUI INOVASI KEMASAN - NATSIR, KHAIRINA; Waani, Alfredo Marthen (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Packaging is one of the weapons in today's business world, including in the culinary industry. Through packaging, consumers are able to provide an assessment of the character and image of the product. Through packaging, manufacturers are able to convey the value, content and benefits of a product. Packaging also influences consumers in making purchasing decisions, therefore packaging is often said to be a silent salesman. Partners in this Community Service activity are SME entrepreneurs in RW 09 Jl. Kano Raya, Kelapa Dua Village, Tangerang. The products produced are culinary products such as pastries, side dishes, chili sauce, Opak, Banana Chips, Seroja Flowers, Roasted Nuts and so on which generally still use the old way of packaging, and have not considered packaging as an advantage that can increase product value. and expand the market. It can be seen that the economic growth of this group has not been accompanied by the skills of the MSME entrepreneurs. Business entrepreneurs are satisfied with sales that are so-so, even though if these culinary products were given a little touch of packaging innovation, it is possible that their businesses will develop with better marketing. So related to this, in this SME’s activity, counseling has been carried out to SME entrepreneurs about packaging innovation so that the value of culinary products can be boosted and provide even better added value for their entrepreneurs. The activity was attended by 20 SME’s participants.